Inhaled, dual release liposomal ciprofloxacin in non-cystic fibrosis bronchiectasis (ORBIT-2): a randomised, double-blind, placebo-controlled trial. Issue 9 (16th May 2013) - Serisier, David J; Bilton, Diana; De Soyza, Anthony; Thompson, Philip J; Kolbe, John; Greville, Hugh W; Cipolla, David; Bruinenberg, Paul; Gonda, Igor; ,
Abstract : Background: The delivery of antipseudomonal antibiotics by inhalation to Pseudomonas aeruginosa -infected subjects with non-cystic fibrosis (CF) bronchiectasis is a logical extension of treatment strategies successfully developed in CF bronchiectasis. Dual release ciprofloxacin for inhalation (DRCFI) contains liposomal ciprofloxacin, formulated to optimise airway antibiotic delivery. Methods: Phase II, 24-week Australian/New Zealand multicentre, randomised, double-blind, placebo-controlled trial in 42 adult bronchiectasis subjects with ≥2 pulmonary exacerbations in the prior 12 months and ciprofloxacin-sensitive P aeruginosa at screening. Subjects received DRCFI or placebo in three treatment cycles of 28 days on/28 days off. The primary outcome was change in sputum P aeruginosa bacterial density to the end of treatment cycle 1 (day 28), analysed by modified intention to treat (mITT). Key secondary outcomes included safety and time to first pulmonary exacerbation—after reaching the pulmonary exacerbation endpoint subjects discontinued study drug although remained in the study. Results: DRCFI resulted in a mean (SD) 4.2 (3.7) log10 CFU/g reduction in P aeruginosa bacterial density at day 28 (vs −0.08 (3.8) with placebo, p=0.002). DRCFI treatment delayed time to first pulmonary exacerbation (median 134 vs 58 days, p=0.057 mITT, p=0.046 per protocol). DRCFI was well tolerated with a similar incidence of systemic adverse events to the placebo group, but fewer pulmonary adverse events. Conclusions: Once-daily inhaled DRCFI demonstrated potent antipseudomonal microbiological efficacy in adults with non-CF bronchiectasis and ciprofloxacin-sensitive P aeruginosa . In this modest-sized phase II study, DRCFI was also well tolerated and delayed time to first pulmonary exacerbation in the per protocol population.